(untitled) (diségno, 2019)
The “International Conference on Modern Age Fortification of the Mediterranean Coast FORTMED, organized by Anna Marotta and Roberta Spallone, took place on October 18th, 19th and 20th 2018 at the Department of Architecture and Design (DAD) of Politecnico di Torino, in the marvelous location of Valentino Castle. Focuses of the conference were researches on modern fortifications in the Mediterranean area